2009
DOI: 10.1104/pp.109.138461
|View full text |Cite
|
Sign up to set email alerts
|

ETR1-Specific Mutations Distinguish ETR1 from Other Arabidopsis Ethylene Receptors as Revealed by Genetic Interaction withRTE1     

Abstract: The plant growth regulator ethylene is perceived by a family of homologous receptors that negatively regulate ethylene responses. It is well established that dominant missense mutations within the ethylene-binding domain of any of these receptors result in ethylene insensitivity (Chang et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Furthermore, in tissues where overexpression of either SlGR or SlGRL1 fails to give rise to an ethylene-insensitive phenotype, it is possible that the appropriate target receptor may be absent, present at reduced levels compared with other receptors, or that the response is mediated by receptors that do not require GR/RTE1 family proteins. The latter hypothesis is supported by the observation that the etr1-9/ers1-3 double null mutant of Arabidopsis remains responsive to ethylene, suggesting that certain ethylene responses are therefore likely to be independent of AtRTE1, given that AtRTE1 acts predominantly through the ETR1 receptor (Resnick et al, 2006;Qu et al, 2007;Zhou et al, 2007;Rivarola et al, 2009).…”
Section: Evidence For the Existence Of Distinct Ethylene Signaling Mosupporting
confidence: 53%
“…Furthermore, in tissues where overexpression of either SlGR or SlGRL1 fails to give rise to an ethylene-insensitive phenotype, it is possible that the appropriate target receptor may be absent, present at reduced levels compared with other receptors, or that the response is mediated by receptors that do not require GR/RTE1 family proteins. The latter hypothesis is supported by the observation that the etr1-9/ers1-3 double null mutant of Arabidopsis remains responsive to ethylene, suggesting that certain ethylene responses are therefore likely to be independent of AtRTE1, given that AtRTE1 acts predominantly through the ETR1 receptor (Resnick et al, 2006;Qu et al, 2007;Zhou et al, 2007;Rivarola et al, 2009).…”
Section: Evidence For the Existence Of Distinct Ethylene Signaling Mosupporting
confidence: 53%
“…Recently it was found that REVERSION TO SENSI-TIVITY1 (RTE1) specifically interacts with ETR1 to modulate ethylene responses in Arabidopsis as a positive regulator of ETR1, but does not regulate the other receptor isoforms (Resnick et al, 2006;Zhou et al, 2007;Rivarola et al, 2009;Dong et al, 2010). Interestingly, rte1 null mutants display phenotypes similar to etr1 null mutants including reduced growth in air, ethylene hypersensitivity, and enhanced growth inhibition to application of ethylene (Resnick et al, 2006).…”
Section: Reversion To Sensitivity1 Modulates Ethylene-stimulated Nutamentioning
confidence: 99%
“…Although the biochemical function of RTE1 is unknown, its action in ethylene signaling seems to involve a physical interaction with ETR1 (Dong et al, 2010) and requires the N-terminal domain of ETR1 (Zhou et al, 2007;Qiu et al, 2012). Interestingly, RTE1 appears to have little or no effect on the other Arabidopsis ethylene receptors (Resnick et al, 2006;Rivarola et al, 2009), but the basis for this specificity is unknown. Expression of the RTE1 gene is somehow regulated by HYPER RECOMBINATION1 (HPR1), a component of the THO/Transcription Export complex that is related to mRNA processing (Xu et al, 2015).…”
Section: How Do the Ethylene Receptors Signal?mentioning
confidence: 99%